A learner's wordlist of Pertame - Swan, Christobel; Cousens, Marlene; Institute for Aboriginal Development (Alice Springs, N.T.) (Alice Springs, NT : Institute for Aboriginal Development, 1993)
Pertame-English wordlist with some sentence examples.
" ... based on a list prepared by Gavan Breen ... as part of a literacy course for the School of Australian Linguistics" -- T.p. verso.
Keywords: Pertame language -- Dictionaries -- English; Arrernte / Aranda language (C8) (NT SG53-02); Pertame language (C8) (NT SF53-14); Pertame people (C8) (NT SF53-14); Arrernte / Aranda people (C8) (NT SG53-02); Language - Vocabulary - Word lists; South Central Northern Territory (NT)